2010
DOI: 10.3892/or_00000675
|View full text |Cite
|
Sign up to set email alerts
|

In vitro modulation of MMP-2 and MMP-9 in human cervical and ovarian cancer cell lines by cytokines, inducers and inhibitors

Abstract: Abstract. Matrix metalloproteinases (MMPs) secreted by cervical and ovarian cancer, especially MMP-2 and MMP-9, play crucial roles in tumor invasion and metastasis. We examined the effect of cytokines, mitogens, inducers and inhibitors on MMP-2 and MMP-9 expression in cervical and ovarian cancer cell lines. Human cervical (HeLa and DoTc2-4510) and ovarian (SK-OV-3) cell lines were cultured in appropriate media. At near confluence, the cells were washed with PBS and incubated in serum-free medium with various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In cervical cancer, dysregulation of MMP-2 and MMP-9 has been widely reported. MMP-2 and MMP-9 expression and activation can be affected by various factors, including cytokines, mitogens, inducers, inhibitors, E6/E7 oncoproteins of human papillomavirus 16 (HPV16), and others (22,23). It was reported that the activation of MMP-2 in cervical cancer tissue could be mediated by a functional complex consisting of α(v)β3 integrin/membrane type-1 metalloproteinase-2 (MT1-MMP)/tissue inhibitor of metalloproteinase-2 (TIMP-2) on tumor cell surface (24).…”
Section: Discussionmentioning
confidence: 99%
“…In cervical cancer, dysregulation of MMP-2 and MMP-9 has been widely reported. MMP-2 and MMP-9 expression and activation can be affected by various factors, including cytokines, mitogens, inducers, inhibitors, E6/E7 oncoproteins of human papillomavirus 16 (HPV16), and others (22,23). It was reported that the activation of MMP-2 in cervical cancer tissue could be mediated by a functional complex consisting of α(v)β3 integrin/membrane type-1 metalloproteinase-2 (MT1-MMP)/tissue inhibitor of metalloproteinase-2 (TIMP-2) on tumor cell surface (24).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metallopeptidases (MMPs) degrade the extracellular matrix and basement membrane (Lengyel et al, 2001), enhancing the spread of cancer cells to distant sites (Shen et al, 2017). MMP2 and MMP9 degrade collagen IV in the extracellular basement membrane (Roomi et al, 2010) and rearrange the extracellular matrix during invasion and migration of cancer cells (Nabeshima et al, 2002;Alaseem et al, 2019). Moreover, active level of MMP2 in cancer cells is related to invasion and metastasis (Celentano et al, 2020).…”
Section: Antitumor Effects Of Plt@zro2 In Vivomentioning
confidence: 99%
“…Among them, MMP-2 and MMP-9 belong to the zinc ion-dependent endopeptidases are found in a wide variety of tissues [10‒12]. MMP-2 and MMP -9 expressions have been correlated with cell invasion and tumor size in several cancers such as lung cancer, breast cancer, cervical cancer and ovarian cancer [13‒15]. MMP-2 and MMP-9 have also been strongly connected with extramedullary infiltrates in adult acute lymphoblastic leukemia (ALL) [16].…”
Section: Introductionmentioning
confidence: 99%